2022
DOI: 10.3389/fimmu.2022.875283
|View full text |Cite
|
Sign up to set email alerts
|

Allele and Haplotype Frequencies of HLA-A, -B, -C, and -DRB1 Genes in 3,750 Cord Blood Units From a Kinh Vietnamese Population

Abstract: The frequencies and diversities of human leukocyte antigen (HLA) alleles and haplotypes are representative of ethnicities. Matching HLA alleles is essential for many clinical applications, including blood transfusion, stem cell transplantation, and tissue/organ transplantation. To date, the information about the frequencies and distributions of HLA alleles and haplotypes among the Kinh Vietnamese population is limited because of the small sample size. In this study, more than 3,750 cord blood units from indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Finally, the significant associations found in the HLA-A*11:01, HLA-B*15:02, and HLA-C*08:01 alleles may reflect the linkage disequilibrium in Asian populations. The frequency of the HLA-A*11:01–B*15:02–C*08:01 haplotype was approximately 8% in Kinh Vietnamese populations, while HLA-A*11:01–B*15:02–C*08:01–DRB1*12:02–DQB1*03:01 was around 2% in Chinese populations . Therefore, the results of our study should be interpreted more conservatively.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Finally, the significant associations found in the HLA-A*11:01, HLA-B*15:02, and HLA-C*08:01 alleles may reflect the linkage disequilibrium in Asian populations. The frequency of the HLA-A*11:01–B*15:02–C*08:01 haplotype was approximately 8% in Kinh Vietnamese populations, while HLA-A*11:01–B*15:02–C*08:01–DRB1*12:02–DQB1*03:01 was around 2% in Chinese populations . Therefore, the results of our study should be interpreted more conservatively.…”
Section: Discussionmentioning
confidence: 62%
“…3 To prevent double counting, we extracted the data for SMX from the study and integrated the results with data from other relevant studies. Finally, the significant associa- 34,35 Therefore, the results of our study should be interpreted more conservatively.…”
Section: Limitationsmentioning
confidence: 82%
“…Comparatively, Do MD et al (Do et al, 2020) reported these two to be 7.92% and 9.41% respectively. Que TN et al (Que et al, 2022) also reported these two alleles to be 7.29% and 10.7% respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The possible explanation may be due to the different regions or the small sample size, which can only reflect a part of the whole population. Interestingly enough, Que TN et al ( Que et al, 2022 ) reported a frequency of 15.11% of HLA-B*15:02 with a sample size of 3750 participants, who were recruited in Northern and North-central Vietnam ( Que et al, 2022 ). Besides, we found the frequencies of HLA-B*38:02 and *46:01 to be equally 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, cord blood samples were collected within 24 h of birth. Before storage, all cord blood samples were checked for the following parameters: no blood cluster or bizarre colours, mean corpuscular volume ≥ 95 fl, no abnormal haemoglobin confirmed by high performance liquid chromatography analysis, number of nucleated cells ≥ 10 9 cells/ml and negative for infectious pathogens, including hepatitis C virus, hepatitis B virus, human immunodeficiency virus, cytomegalovirus and bacteria (Que et al., 2022).…”
Section: Methodsmentioning
confidence: 99%